BUGIS CULTURE DECONSTRUCTION IN NOVEL LA GALIGO 2 - Musliadi, Musliadi; Yunus, Reski Yusrini Islamiah (Literature and Literacy, 2023)
The representation of Bugis culture in La Galigo 2 illustrates the ancient Bugis people's way of life during the Bugis kingdom in South Sulawesi. Historically, the epic La Galigo, which inspired La Galigo 2, describes Bugis culture, an indigenous culture of Indonesia. This study aims at describing the portrayal of Bugis Culture deconstruction in the novel Lagaligo 2 from the perspective of life order and beliefs. The analytical method used deconstruction theory through the perspective of Derrida. The results of the analysis show that the cultural representation of Bugis in the novel La Galigo shows several variations of ancient Bugis culture. Bissu people, who live in numerous South Sulawesi locations, can speak with God. The special ritual of the bissu people is known as the bissu dance (maggirik). The term walasuji is a gate building made of woven bamboo, used by the Bugis for traditional parties, but now walasuji is used only for weddings for the Bugis. In addition, the ancient Bugis people sprinkled bertih on visitors in the welcoming ceremony as a symbol of respect and safety. Mutual respect for the Bugis is determined by the social strata that the nobility call puang or opu. The ancient Bugis people believed in the Dewata (God), Sang Patotoqe, but over time this belief began to erode because they had embraced a particular religion. The novel La Galigo 2 implies that in central Indonesia there is a mythology about the ancient Bugis community and the richness of Indonesia’s local culture.